Polymorphism analysis of tyrosine hydroxylase (TH) in military working dogs - Eo, Jungwoo; Choi, Bong-Hwan; Jung, Yi-Deun; Kwon, Yun-Jeong; Kim, Tae-Hun; Seong, Hwan-Hoo; Kim, Heui-Soo (Genes & genomics, 2013)
Canine and human behavior are shaped by similar evolutionary processes, yet the identification of the behavioral phenotype is often difficult. A widely used method relies on breed stereotypes provided by experts such as dog trainers. To reveal a valid association between behavior and genetic factors, an association study of behavioral phenotyping and genotyping is essential. We screened for variable number of tandem repeat (VNTR) polymorphisms in intron 4 of the tyrosine hydroxylase gene in military working dogs (belonging to pass and fail groups based on the results of an in-training examination conducted by the drillmaster), which were scored based on possessiveness, audaciousness, concentration, and motor ability by qualification examination. We first characterized each genotype by sequencing, in which the 1/1 type consists of a single copy of a 36-bp sequence and the 2/2 type is a duplicated form of the 36-bp repeat unit. The 1/2 alleles showed a single nucleotide change as a heteroduplex, which generated a PCR product of similar size as that of the 1/1-182-bp. The military working dogs showed the 2/2 type of VNTR and heteroduplex. For the pass group, two dogs possessed 2/2 type (40 %), whereas three dogs were of the heteroduplex type (60 %). However, all members of fail group showed the 2/2 type (100 %). These data indicate that repeat polymorphisms with behavioral phenotyping can identify military working dogs that would pass or fail the in-training examination.